PENGARUH LATIHAN V-DRILL DAN T-DRILL TERHADAP KEMAMPUAN SMASH DALAM PERMAINAN BULUTANGKIS PADA ATLET PB. JURIT LOMBOK TIMUR - wahyu dwi cahyanto putera; Johan Irmansyah; Aminullah (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2023)
This study aimed to determine the effect of V-Drill and T-Drill exercises on smash ability in badminton among athletes of PB. Jurit East Lombok in 2023. The study employed an experimental method using a one-group pretest-posttest design, applied separately to two experimental groups. The population consisted of 20 male athletes, while the sample included 12 participants. The treatment was administered through V-Drill and T-Drill exercises for 12 sessions. Data were collected using a smash accuracy test and analyzed using a paired sample t-test. The results showed that V-Drill training had a significant effect on smash ability, with t-count 4.583 > t-table 2.015 at the 5% significance level. Likewise, T-Drill training also had a significant effect on smash ability, with t-count 7.889 > t-table 2.015. Based on these findings, it can be concluded that both V-Drill and T-Drill exercises significantly improve the smash ability of badminton athletes at PB. Jurit East Lombok.